2017
DOI: 10.1111/jfpp.13206
|View full text |Cite
|
Sign up to set email alerts
|

Potential uses of sweet potato-wheat composite flour in the pastry industry based on proximate composition, physicochemical, functional, and sensory properties of four pastry products

Abstract: The nutritional, physicochemical, functional properties of sweet potato‐wheat composite flour and its sensory attributes in four pastry products were studied. Moisture content of 100% sweet potato flour was significantly (p < .001) lower than 100% wheat flour and sweet potato‐wheat composite flours (5%, 10%, 15%, 20%, and 30%). The 100% sweet potato flour had 89.2% carbohydrate and 378.6 kcal of energy per 100 g. The pH of 100% sweet potato flour was significantly (p < .05) lower, compared to 100% wheat flour.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
4
8
2
Order By: Relevance
“…The ash determination provides an indication of the sample's richness in mineral elements; the sample evaluated had an ash content of 3.61%. Tortoe et al (2017) found 4% ash content, a value close to that found in the present study.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The ash determination provides an indication of the sample's richness in mineral elements; the sample evaluated had an ash content of 3.61%. Tortoe et al (2017) found 4% ash content, a value close to that found in the present study.…”
Section: Resultssupporting
confidence: 92%
“…Values were close to those found by Tortoe et al. (2017) in sweet potato flour, where protein, fat, and carbohydrate were 3.84%, 0.7%, and 89.2%, respectively, indicating this is an energetic food.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Shittu [10] also agreed with that as the composite flours used were either binary or ternary mixtures of flours from some other crops with or without wheat flour. Flour from these root and tuber crops have been used in the production of bread, cookies, doughnuts and noodles [11,12]. The use of composite flours in bread making has been reported by many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of flour depends on its moisture content and conditions of storage (Van Hal, 2000). Lower moisture content enhances desirable characteristics of the flour and avoids caking which affects its functional properties and quality (Tortoe et al, 2017). Flours with moisture contents lower than 14% are capable of preventing microbial growth, thereby maximizing the shelf-life (Teye et al, 2018).…”
Section: Proximate Composition Of Composite "Fufu" Flourmentioning
confidence: 99%